Synthesis of plus strands of retroviral DNA in cells infected with avian sarcoma virus and mouse mammary tumor virus. - Kung, H J (1981)
The vast majority of plus strands synthesized in quail cells acutely infected with avian sarcoma virus were subgenomic in size, generally less than 3 kilobases (kb). A series of discrete species could be identified after agarose gel electrophoresis by annealing with various complementary DNAs, indicating specificity in the initiation and termination of plus strands. The first plus strand to appear (within 2 h postinfection) was similar in length to the long redundancy at the ends of linear DNA (0.35 kb), and it annealed with complementary DNAs specific for the 3' and 5' termini of viral RNA (Varmus et al., J. Mol. Biol. 120:50-82, 1978). Several subgenomic plus-strand fragments (0.94, 1.38, 2.3, and 3.4 kb) annealed with these reagents. At least the 0.94- and 1.38-kb strands were located at the same end of linear DNA as the 0.35-kb strand, indicating that multiple specific sites for initiation were employed to generate strands which overlapped on the structural map. We were unable to detect RNA liked to plus strands isolated as early as 2.5 h postinfection; thus, the primers must be short (fewer than 50 to 100 nucleotides), rapidly removed, or not composed of RNA. To determine whether multiple priming events are a general property of retroviral DNA synthesis in vivo, we also examined plus strands of mouse mammary tumor virus DNA in chronically infected rat cells after induction of RNA and subsequent DNA synthesis with dexamethasone. In this case, multiple, discrete subgenomic DNA plus strands were not found when the same methods applied to avian sarcoma virus DNA were used; instead, the plus strands present in the linear DNA of mouse mammary tumor virus fell mainly into two classes: (i) strands of ca. 1.3 kb which appeared early in synthesis and were similar in size and genetic content to the terminally repeated sequence in linear DNA; and (ii) plus strands of the same length as linear DNA. A heterogeneous population of other strands diminished with time, was not found in completed molecules, and was probably composed of strands undergoing elongation. These two retroviruses thus appear to differ with respect to both the number of priming sites used for the synthesis of plus strands and the abundance of full-length plus strands. On the other hand the major subgenomic plus strand of mouse mammary tumor virus DNA (1.3 kb) is probably the functional homolog of a major subgenomic plus strand of avian sarcoma virus DNA (0.35 kb). The significance of this plus strand species is discussed in the context of current models which hold that it is used as a template for the completion of the minus strand, thereby generating the long terminal redundancy.